Willing Workers and other stories - Parker, Carol (University Press Plc, 2008)
Willing Workers, The Capture of a thief, Story of Shola and Shola Returns Home are four stories of adventure which take place in and around Lagos, and the surrounding towns and fishing villages of the coast and creeks.
Keywords: Adventure; Fiction; Juvenile Literature